2007
DOI: 10.1021/je060436f
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Stability of H2 + Tetrahydrofuran Mixed Gas Hydrate in Nonstoichiometric Aqueous Solutions

Abstract: Phase equilibria (pressure−temperature relations) of the H2 + tetrahydrofuran mixed gas hydrate system have been measured for various concentrations of tetrahydrofuran aqueous solutions. The three-phase equilibrium lines obtained in the present study are shifted to the low-temperature or high-pressure side from that of the stoichiometric THF solution. Each three-phase equilibrium line of H2 + tetrahydrofuran hydrate converges at the three-phase equilibrium line of the pure tetrahydrofuran hydrate. At the cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
150
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(187 citation statements)
references
References 17 publications
28
150
1
Order By: Relevance
“…Results from a series of calorimetry experiments suggested that THF forms a binary hydrate with H 2 ; results for TBAB were not definitive. The measured THF+H 2 hydrate stability data agreed well with the results of Hashimoto et al [26] and Anderson et al [27]. To confirm that binary THF + H 2 hydrates had formed in the calorimetry experiments, Raman spectra were taken at different points of the hydrate synthesis process using a separate facility.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Results from a series of calorimetry experiments suggested that THF forms a binary hydrate with H 2 ; results for TBAB were not definitive. The measured THF+H 2 hydrate stability data agreed well with the results of Hashimoto et al [26] and Anderson et al [27]. To confirm that binary THF + H 2 hydrates had formed in the calorimetry experiments, Raman spectra were taken at different points of the hydrate synthesis process using a separate facility.…”
Section: Discussionsupporting
confidence: 85%
“…Calorimetry results for binary hydrate formed from aqueous solutions of TBAB are shown in Figures 14 and 15. TBAB has been proposed to reduce the formation pressure of H2 hydrate [6,21,22]. TBAB is known to form semi-clathrate hydrate in which the water cage is broken to accommodate the large TBAB molecule [23].…”
Section: Calorimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…(6b). This Raman shift agrees with that of H 2 encaged in the S-cage of s-II hydrate [6,7]. That is, H 2 can selectively occupy the S-cage of s-II hydrate generated from H 2 + propane + water mixture, while propane occupies the L-cage entirely.…”
Section: Raman Spectroscopic Analysis For H 2 + Hydrocarbon + Water Msupporting
confidence: 80%
“…The mixed-gas hydrate systems containing H 2 and suitable additives enable us to perform the H 2 storage at much lower pressure conditions than the pure H 2 hydrate. Tetrahydrofuran (hereafter, THF) is the most familiar of such additives [3][4][5][6][7][8]. In addition, quaternary ammonium salts [6,[9][10][11][12], cyclic hydrocarbons [13] and so on have been reported.…”
Section: Introductionmentioning
confidence: 99%